Changes in the population of methicillin-resistant Staphylococcus pseudintermedius and dissemination of antimicrobial-resistant phenotypes in the Netherlands - Duim, Birgitta; Verstappen, Koen M.; Broens, Els M.; Laarhoven, Laura M.; Van Duijkeren, Engeline; Hordijk, Joost; De Heus, Phebe; Spaninks, Mirlin; Timmerman, Arjen J.; Wagenaar, Jaap A. (American Society for Microbiology, 2016)
Methicillin-resistant Staphylococcus pseudintermedius (MRSP), which is often multidrug resistant (MDR), has recently emerged as a threat to canine health worldwide. Knowledge of the temporal distribution of specific MRSP lineages, their antimicrobial resistance phenotypes, and their association with clinical conditions may help us to understand the emergence and spread of MRSP in dogs. The aim of this study was to determine the yearly proportions of MRSP lineages and their antimicrobial-resistant phenotypes in the Netherlands and to examine possible associations with clinical conditions. MRSP was first isolated from a canine specimen submitted for diagnostics to the Faculty of Veterinary Medicine of Utrecht University in 2004. The annual cumulative incidence of MRSP among S. pseudintermedius increased from 0.9% in 2004 to 7% in 2013. MRSP was significantly associated with pyoderma and, to a lesser extent, with wound infections and otitis externa. Multilocus sequence typing (MLST) of 478 MRSP isolates yielded 39 sequence types (ST) belonging to 4 clonal complexes (CC) and 15 singletons. CC71 was the dominant lineage that emerged since 2004, and CC258, CC45, and several unlinked isolates became more frequent during the following years. All but two strains conferred an MDR phenotype, but strains belonging to CC258 or singletons were less resistant. In conclusion, our study showed that MDR CC71 emerged as the dominant lineage from 2004 and onward and that less-resistant lineages were partly replacing CC71.